Telemonitoring in subjects with newly diagnosed heart failure with reduced ejection fraction: From clinical research to everyday practice. (April 2019) - Koulaouzidis, G; Barrett, D; Mohee, K; Clark, AL
Introduction: Heart failure is increasingly common, and characterised by frequent admissions to hospital. To try and reduce the risk of hospitalisation, techniques such as telemonitoring (TM) may have a role. We wanted to determine if TM in patients with newly diagnosed heart failure and ejection fraction <40% reduces the risk of readmission or death from any cause in a 'real-world' setting. Methods: This is a retrospective study of 124 patients (78.2% male; 68.6 ± 12.6 years) who underwent TM and 345 patients (68.5% male; 70.2 ± 10.7 years) who underwent the usual care (UC). The TM group were assessed daily by body weight, blood pressure and heart rate using electronic devices with automatic transfer of data to an online database. Follow-up was 12 months. Results: Death from any cause occurred in 8.1% of the TM group and 19% of the UC group ( p = 0.002). There was no difference between the two groups in all-cause hospitalisation, either in the number of subjects hospitalised ( p = 0.7) or in the number of admissions per patient ( p = 0.6). There was no difference in the number of heart-failure-related readmissions per person between the two groups ( p = 0.5), but the number of days in hospital per person was higher in the UC group ( p = 0.03). Also, there were a significantly greater number of days alive and out of hospital for the patients in the TM group compared with the UC group ( p = 0.0001). Discussion: TM is associated with lower any-cause mortality and also has the potential to reduce the number of days lost to hospitalisation and death.